MATHEMATICAL MODELING OF THERMO-REGULATION OF FUEL IN DIESEL ENGINES YaMZ-238* - & et al., Al – Maidi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The Maintaining the temperature system for fuel diesel engine by mathematical modeling. Thermal control of fuel with objective of this research, Peltier thermal application and paraffin-based thermal batteries. A fuel system thermometer is assembled in the diesel engine and thermal controller. A thermal model for thermal control of fuel has been developed in the diesel engine. Mathematical model is a system of differential equations. The use of controller for thermal control system of fuel and engine oil depending on the software obtained by approximating the graphical solution of the system allow to maintain the temperature with a error of ± 3 ° C for fuel and engine oil, which corresponds to the values ​​obtained experimentally . The upgraded thermal control system can be used for existing and newly designed diesel engines. The production tests for diesel engine YaMZ-238 (BF and Deutz BF 6M 2012 C analogue with water cooling) revealed an improvement in eco-ecological characteristics of diesel engine operation: a 20% reduction in fuel consumption during start-up and operation of deceleration from 7 to 15%, exhausted gas toxicity from 10 to 17%. The developed mathematical model could be use to analyze the temperature systems of dual-fuel diesel engines on diesel and gas.